Attitudes towards water conservation: Evidence from households in Germany - Manuel Frondel; Delia Niehues; Valerie Peetz; Stephan Sommer; Lukas Tomberg (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Based on randomized information treatments that were embedded in a large online survey among more than 6,000 single-home owners from Germany, we investigate the malleability of attitudes towards water conservation and a variety of conservation policies. While the empirical results indicate that, generally, respondents have a positive attitude towards water conservation, this positive attitude is merely slightly lowered by information treatments that included either nuanced or negatively biased information about the necessity of water conservation. In addition, we find that respondents attribute a higher level of concern for water conservation to themselves than to both people in their personal environment and the population in general. Conservation policies, such as education campaigns, price increases for heavy consumers and comparison reports on water consumption are accepted by the majority of respondents and perceived as fair, whereas smart water tariffs and frequent price increases are largely rejected. – – Auf der Grundlage von randomisierten Informationsbehandlungen, die in eine große Online-Umfrage unter mehr als 6.000 Einfamilienhausbesitzern in Deutschland eingebettet waren, untersuchen wir die Formbarkeit von Einstellungen zum Wassersparen und zu einer Reihe von Einsparungsmaßnahmen. Während die empirischen Ergebnisse darauf hindeuten, dass die Befragten im Allgemeinen eine positive Einstellung zum Wassersparen haben, wird diese positive Einstellung durch Informationsbehandlungen, die entweder nuancierte oder negativ verzerrte Informationen über die Notwendigkeit des Wassersparens enthielten, nur geringfügig gesenkt. Darüber hinaus stellen wir fest, dass die Befragten sich selbst ein höheres Maß an Sorge um die Wassererhaltung zuschreiben als den Menschen in ihrem persönlichen Umfeld und der Bevölkerung im Allgemeinen. Sparmaßnahmen wie Aufklärungskampagnen, Preiserhöhungen für Großverbraucher und Vergleichsberichte über den Wasserverbrauch werden von der Mehrheit der Befragten akzeptiert und als gerecht empfunden, während intelligente Wassertarife und häufige Preiserhöhungen weitgehend abgelehnt werden.
Keywords: D12; Q25; Q58; 330; Information experiment; policy approval; water conservation policy